Psychological Well-Being Peserta Didik Fase E SMA Negeri 10 Semarang - Harjani, Tri; Venty, Venty; Susiati, Susiati (Journal Prakarsa Paedagogia, 2023)
The purpose of this research is to find out the psychological well-being of Phase E students or class X SMA Negeri 10 Semarang. The research sample was Phase E or X class students with a total of 354 (113 boys and 241 girls). The researcher used incidental techniques to collect samples. Research using descriptive quantitative method. To find out the well-being of students, the researcher used the psychological well-being scale instrument, or PWBS, which was developed by Ryff (1989) and has been re-translated by the author, distributed via an online system via Google form. The total number of items 84 are all valid items, the validity coefficient is from 0.314 to 0.779 and the reliability coefficient is 0.966. 13 (3.7%) students had a low psychological well-being category, 125 (35.3%) the lower medium category, 180 (50.8%) the upper medium category and 36 (10.2%) the high category. The main concern is students who have the middle and low categories. It is necessary to develop a Guidance and Counseling service program to improve psychological well-being in order to increase the level of the impaired to the optimal level.